NAVIGATING ARTIFICIAL INTELLIGENCE’S FUTURE IN BUSINESS BY EXAMINING THE CONFLUENCE OF AI AND ENTREPRENEURSHIP: PERSPECTIVES FROM YOUNG ENTREPRENEURS - Ijaz Latif; Khawaja Hisham Ul Hassan (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
This paper goes into profound mutual relation between AI and entrepreneurship, based on the insights given by young entrepreneurs. Current research often emphases on well-known business leaders and experts, ignoring the extraordinary viewpoints of young entrepreneurs. This study employed the qualitative research design. The purpose of this study is to explore the point of view and different perspectives of young entrepreneurs about the convergence of AI and entrepreneurship by conducting semi structured interviews to collect the data. The data driven form interviews presented a pleasant knitted relation between the entrepreneurial journey and AI technological integration. The integration of artificial intelligence has transformed conventional business practices to more advanced tools, resulting in increased effectiveness, reduced expenses, and better decision making. This research found that AI adoption in daily business operations has given a lifeline to new entrepreneurs to compete against the corporate businesses, this finding was the mainstay of the interviews given by the young business persons for this paper.